Phenotypic and genotypic detection of carbapenem-resistant Gram negative bacteria from different clinical samples in a tertiary care hospital. - Prem prakash Singh, Dr. Munesh Kumar Sharma, Yogesh kumar pant, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Carbapenems represent the sole class of beta-lactam antibiotics that remain effective against pathogensproducing extended-spectrum beta-lactamases (ESBLs). This critical efficacy has led to an increasing reliance on carbapenems, not only for treating identified infections but also for providing empirical therapy to patientsin intensive care units (ICUs) who acquire infections. Consequently, the frequent use of these medications has created a significant selective pressure